CONTEXTUAL ANALYSIS OF THE INTERROGATIVE SENTENCE IN ENGLISH LANGUAGE - Saidova Mamura (Western European Studies, 2025)
This article examines the contextual functions and pragmatic roles of interrogative sentences in the English language. Interrogatives, beyond their syntactic form and primary function of requesting information, perform a wide range of communicative tasks such as expressing doubt, politeness, irony, or rhetorical effect. The paper explores different types of interrogative constructions—yes/no questions, wh-questions, tag questions, and alternative questions— analyzing how their interpretation is shaped by discourse context, intonation, and speaker intent. Drawing on examples from both spoken and written English, the study highlights the role of context in disambiguating function and meaning, particularly in cases where interrogatives serve indirect speech acts or convey emotional undertones. This analysis contributes to a deeper understanding of English interrogative syntax and pragmatics, offering insights relevant to translation, discourse analysis, and language pedagogy.
Keywords: Interrogative sentences; Contextual meaning